CYTOLOGICAL EXAMINATION OF EXPERIMENTAL PURULENT WOUNDS IN THE TREATMENT OF SILVER NANOPARTICLES IN ULTRASOUND CAVITATION - P. F. Myronov; V. I. Bugaiov; O. O. Tymakova; M. V. Pogorielov; A. S. Opanasyuk (Eastern Ukrainian Medical Journal, 2019)
The treatment of purulent wounds is an important problem of modern surgery. Antibiotic resistance of bacteria dramatically reduces the effectiveness of traditional methods of treatment. Previous studies have indicated that silver nanoparticles have good antibacterial activity and do not cause bacterial resistance. Low-frequency ultrasound improves the bactericidal properties of nanoparticles, as well as plays an important role in cleaning wounds from purulent-necrotic tissue and delivering nanoparticles to the site of infection. The combination of the properties of silver nanoparticles and low-frequency ultrasound requires careful investigation in the treatment of purulent wounds. The purpose of the study was to substantiate the effectiveness of the treatment of purulent wounds with silver nanoparticles and low-frequency ultrasound by cytological examination. Materials and Methods. This study was carried out on 60 laboratory rats, which were equally divided into 3 groups. In the first group, treatment was carried out by low-frequency ultrasound; in the second group, a solution of silver nanoparticles was used together with low-frequency ultrasound; in the third, control group, a 0.05% Chlorhexidine solution was used. Silver nanoparticles with a size of 10-60 nm were synthesized by the polyol method. Results. The study showed that there were no statistically significant differences between the ultrasound, silver nanoparticles/ultrasound and Chlorhexidine groups on the first day. On the third day, a statistically significant increase in phagocytic neutrophilic leukocytes and fibroblasts was observed in the silver nanoparticles/ultrasound group compared with the first day. In comparison with the Chlorhexidine group, the number of monocytes (2.2 and 4.2 times) and macrophages (1.4 and 1.9 times) increased in the ultrasound and silver nanoparticles/ultrasound groups respectively, and the necrotic type of cytograms was not determined. On the seventh day, granulation tissue began to appear in the silver nanoparticles/ultrasound group, the percentage of leukocyte destruction decreased (by 4.5 times), microorganisms were almost not detected, regenerative types of cytograms appeared for the first time. The number of neutrophils in the control group exceeded the analogous parameter of the ultrasound group by 2.4 times and the silver nanoparticles/ultrasound group by 3.8 times. The number of fibroblasts became significantly larger in the ultrasound (2.2 times) and the silver nanoparticles/ultrasound (2.3 times) groups, compared with the group where Chlorhexidine was used. On the tenth day, the number of fibroblasts and cells of the monocytic-macrophage series increased in the control group, which indicates later regenerative processes. On the tenth day, there was a complete epithelization of wounds in the silver nanoparticles/ultrasound group, while healing occurred on day 12 in the ultrasound group, and on day 21 in the control group. Conclusions. The combined use of silver nanoparticles and low-frequency ultrasound significantly improves the cytological parameters of wound healing of purulent wounds and has clear advantages over the ultrasound monotherapy and the use of Chlorhexidine. The presented method reduces the treatment time and can be prospectively introduced into surgical practice.